Indigenous Communities’ Spatial Perceptions of the Concepts of “Sacred Space” and “Profane Space” A Study of the Traditional Village of Beleq Gumantar - Muhammad Agung Bahroni; Antariksa Antariksa; Yusfan Adeputera Yusran (Abdi Masyarakat, 2026)
Space is an important element in indigenous communities because it reflects cultural values, belief systems, and patterns of social life. This study aims to analyze indigenous community perceptions of sacred and profane spaces in the Beleq Gumantar Traditional Village, North Lombok Regency, identify the forms and meanings of spaces perceived as sacred or profane, and explain how these perceptions influence spatial utilization practices. The research employed a qualitative approach with a phenomenological method. Data were collected through field observations, in-depth interviews, and documentation involving traditional leaders, religious leaders, cultural custodians, and community members. Data analysis was conducted using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results indicate that the indigenous community has a clear perception of the distinction between sacred and profane spaces. Sacred spaces are associated with ritual activities, religious practices, and ancestral reverence, while profane spaces are used for social, economic, and domestic activities. These perceptions influence patterns of spatial utilization, accessibility, and customary regulations governing the use of space. The study also reveals that perceptions of sacred and profane spaces contribute to maintaining social order, preserving cultural identity, and sustaining traditional spatial systems despite the challenges posed by modernization. This research contributes to the understanding of spatial perception in indigenous communities and provides insights for cultural heritage preservation and culturally based spatial planning.